2020
DOI: 10.3389/fendo.2020.577745
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Gene Sequence Divergence, Expression Dynamics, and Endocrine Regulation of the Vitellogenin Gene Family in the Whiteleg Shrimp Litopenaeus vannamei

Abstract: In this report, we studied the vitellogenin gene family in the whiteleg shrimp Litopenaeus vannamei by transcriptomics, bioinformatics, and molecular biology methods. At least three moderately homologous vitellogenin (Vg) genes (i.e. LvVg1, LvVg2, and LvVg3) were identified in the genome. The deduced LvVg proteins consisted of a vitellogenin_N domain, a DUF1943 domain, and a VWD domain typical of most vitellogenins from oviparous animals. LvVg1 was the most abundant Vg expressed in the hepatopancreas and ovary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…v a n n a m e i g e n o m e a n d XR_003475567.1 and XM_027379601.1, respectively, as previously reported (Dai et al, 2021). Different Vg genes and multiple Vg isoforms with different expression patterns have been found in L. vannamei (Wang et al, 2020). However, their contribution to vitellin accumulation in oocytes is unclear.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…v a n n a m e i g e n o m e a n d XR_003475567.1 and XM_027379601.1, respectively, as previously reported (Dai et al, 2021). Different Vg genes and multiple Vg isoforms with different expression patterns have been found in L. vannamei (Wang et al, 2020). However, their contribution to vitellin accumulation in oocytes is unclear.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, the results of the current study showed that the signal peptide was only found in the a.a. sequences of Ov-Vg but not Hp-Vg (Figure 6B). It is speculated that Hp-Vg is transported from the hepatopanscreas to the ovary via the vitellogenin apolipoprotein, which does not require a signal peptide (Wang et al, 2020). In contrast, Ov-Vg is secreted and absorbed by ovaries independently via a paracrine pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a certain amount of Vg protein could also be detected in hemolymph of subadult shrimp, however, the levels were lower than in adults ( 27 , 61 ). Hepatopancreas and ovary have been known as the site of vitellogenesis ( 62 – 64 ), and multiple Vg genes have been reported in some species, including Pandalopsis japonica ( 65 ), Metapenaeus ensis ( 66 ) and L. vannamei ( 67 ). In M. ensis , expression level of MeVg1 was relatively high in HP but low in ovary ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional expression of L. vannamei Vg mRNA in the incubated ovarian explants was determined using QuantiFast Probe RT-PCR + ROX Vial Kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions. For the design of primers and probes, we utilized a cDNA sequence by encoding the Vg gene that was frst reported by Raviv et al [15] (GenBank ID: AY321153), which also corresponds to LvVg1b and LvVg1e of the LvVg1 gene group, as reported by [16]. Total RNAs extracted from the incubated ovarian explants with RNeasy Mini Kit (250) (Qiagen, Hilden, Germany) were used as templates.…”
Section: Methodsmentioning
confidence: 99%